The Aging Epigenome and The Rejuvenation Strategies - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Aging is an unavoidable part of life, defined by a gradual loss in tissue and organ function and an increasing chance of death. Current studies of aging connected the genetic and epigenetic changes to cause this process.CONTENT: When the aging-related epigenetic alterations is accumulated, it may result in irregulated gene expression, metabolic instability, stem cell senescence and exhaustion, and imbalance of tissue homeostasis, which all accelerate the aging process. Altered epigenetic gene regulatory mechanisms such as DNA methylation, histone modification and chromatin remodeling, and non-coding RNAs can induce aging process, thus manipulating these processes give a chance for the success of age-delaying interventions.SUMMARY: Given updated tools and technologies to investigate the epigenetic regulation affecting aging processes, new therapeutic strategies to delay this process can be developed to increase longevity and improve quality of life.KEYWORDS: aging, epigenetic, senescence, autophagy, mitochondria, metabolism, rejuvenation